1983
DOI: 10.1093/bja/55.5.423
|View full text |Cite
|
Sign up to set email alerts
|

Single Injection Spinal Anaesthesia With Amethocaine and Morphine for Transuretheral Prostatectomy

Abstract: The intrathecal administration of amethocaine plus morphine as an anaesthetic technique for providing surgical anaesthesia and postoperative analgesia was evaluated in 24 patients undergoing transurethral resection of the prostate. The efficacy of the technique was compared with that observed following spinal anaesthesia with amethocaine alone. Twelve patients (group I) received spinal anaesthesia with amethocaine 12-14 mg and a further 12 patients (group II) received spinal anaesthesia with amethocaine 12-14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Since the first clinical use of intrathecal morphine in 1979, several studies have shown the benefits of intrathecal opioids as adjuvants to local anesthetics in providing postoperative pain relief. [ 4 5 6 7 8 9 10 11 12 13 14 15 16 17 ] However, redistribution by rostral spread following intrathecal administration results in several adverse effects such as nausea, vomiting and respiratory depression that become limiting factor in the use of intrathecal opioids. [ 18 19 ] Therefore, several spinal adjuvant drugs such as α 2 agonists (clonidine or dexmedetomidine) have been studied as alternatives to intrathecal opioids.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first clinical use of intrathecal morphine in 1979, several studies have shown the benefits of intrathecal opioids as adjuvants to local anesthetics in providing postoperative pain relief. [ 4 5 6 7 8 9 10 11 12 13 14 15 16 17 ] However, redistribution by rostral spread following intrathecal administration results in several adverse effects such as nausea, vomiting and respiratory depression that become limiting factor in the use of intrathecal opioids. [ 18 19 ] Therefore, several spinal adjuvant drugs such as α 2 agonists (clonidine or dexmedetomidine) have been studied as alternatives to intrathecal opioids.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a low dose (0.1-0.25 mg) of intrathecal morphine has been used to reduce the possible complications and side effects of morphine [1]. Spinal anesthesia with such a low dose of morphine has proven to be safe and effective for a hemorrhoidectomy [2], Caesarean section [3], tubal ligation [4], transurethral prostatectomy [5] and orthopedic surgery [6]. The biggest challenge in a hemorrhoidectomy is to control pain after surgery.…”
mentioning
confidence: 99%